PENGARUH MODEL SELF DIRECTED LEARNING TERHADAP HASIL BELAJAR SISWA PAI PADA MASA PANDEMI - Wulandari, Tri; Ikhtiono, Gunawan; Asmahasanah, Salati (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstract. The application of the self-directed learning model in the learning process that prioritizes students’ independence, activeness and responsibility to obtain improved learning outcomes, either from students’ understanding, attitudes or skills. This study aims to determine the average control and experimental classes and determine the effect of the application of the model. The research method used is a quasi-experimental method, providing an overview of student learning outcomes and the influence of the applied model. The results showed that: 1) the average learning outcomes of the experimental class using the self-directed learning model in the cognitive aspect was 84.75 and the affective aspect was 80.19. 2) there is a significant influence between the self-directed learning model on the learning outcomes of Islamic Religious Education (PAI) students in the cognitive aspect. There is also a significant influence between the self-directed learning model on PAI student learning outcomes in the affective aspect. This self-directed learning model can be used as an alternative for teachers in the PAI learning process.Abstrak. Penerapan model self directed learning pada proses pembelajaran yang mengutamakan kemandirian, keaktifan dan tanggung jawab siswa sehingga memperoleh hasil belajar yang meningkat baik dari pemahaman, sikap maupun keterampilan siswa. Penelitian ini bertujuan untuk mengetahui rata-rata kelas kontrol dan eksperimen serta mengetahui pengaruh penerapan model tersebut. Metode penelitian yang digunakan adalah metode kuasi eksperimen, memberikan gambaran hasil belajar siswa dan pengaruh dari model yang diterapkan. Hasil penelitian menunjukkan bahwa: 1) rata-rata hasil belajar kelas eksperimen dengan menggunakan model Self directed learning pada aspek kognitif sebesar 84,75 dan pada aspek afektif sebesar 80,19. 2) terdapat pengaruh yang signifikan antara model Self directed learning terhadap hasil belajar siswa Pendidikan Agama Islam (PAI) pada aspek kognitif. Kemudian terdapat pengaruh yang signifikan antara model Self directed learning terhadap hasil belajar siswa PAI pada aspek afektif. Model self directed learning ini dapat dijadikan alternatif guru dalam proses pembelajaran PAI.